The Power Consumption Performance of an Orbiting Screw Solid-Solid Mixer - Senda, Semuel Pati; Renanto, Renanto; Roesyadi, Achmad; Sumaryono, Wahono; Bindar, Yazid (Journal of Engineering and Technological Sciences, 2012)
In this work we have investigated mixing in a modified orbiting screw mixerÂ  (MOSM)Â  designedÂ  forÂ  solid-solid mixing.Â  MixingÂ  wasÂ  carriedÂ  outÂ  using urea powder and natural zeolite powder (UZ) of three varying particle sizes (50-60, 60-80 and 80 mesh). Power consumption was calculated from the measured torque of orbit and screw, obtained from computerized records. It was found that theÂ  mixingÂ  processÂ  inÂ  theÂ  modifiedÂ  orbitingÂ  screwÂ  mixerÂ  withÂ  airÂ  injection required a lower power consumption for each particle-size group when compared to mixing without air injection. With UZ mixing in MOSM withÂ  air injection, the lowest E was obtained forÂ  the 60-80 mesh particle-size groupÂ  (4,297 Joule/kg-1),whereas when mixing withoutÂ  air injection, the value wasÂ  10,296 J/kg. The best mixingÂ  operation in this experiment was achieved at NFrÂ  =Â  1.18x10-3 and in the rangeÂ  ofÂ  valuesÂ  NReâÂ  8.77x107 toÂ  2.63x108.Â  Moreover,Â  in thisÂ  study,Â  weÂ  have developedÂ  anÂ  equationÂ  toÂ  estimate theÂ  powerÂ  consumption requiredÂ  forÂ  mixing and determined its correlation with dimensionless numbers.